Monday
March 27, 2017

Post a New Question

Posted by on .

Simplify the following expression, and rewrite it in an equivalent form with positive exponents.
-14xy / 42x^5y^8

  • Math - ,

    -14xy/42x^5y^8
    =-1/3 x^(1-5) y^(1-8)
    =-1/3 x^-4 y^-7
    =-1/[3(x^4y^7)]

  • Math - ,

    -14xy/42x^5y^8

    42=3*14

    -14/42= -14/(3*14)= -1/3


    -14xy/42x^5y^8 =

    -xy/3x^5y^8

    Multiply with x^5*y^8

    -xy/3x^5y^8= -x*y*x^5*y^8/3=
    -x^6*y^9/3

    -14xy/42x^5y^=-xy/3x^5y^8=-x^6*y^9/3

  • Math - ,

    alx answer is wrong

  • Math - ,

    -14xy/42x^5y^8= -xy/3x^5y^8= -x^6*y^9/3

  • Math - ,

    "-14xy/42x^5y^8= -xy/3x^5y^8= -x^6*y^9/3"

    please check your answer.

  • Math - ,

    please help me with the factorization,findin the middle term

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question